Coxsackievirus A6 Induces Cell Cycle Arrest in G0/G1 Phase for Viral Production - Wang, Zengyan; Wang, Yue; Wang, Shaohua; Meng, Xiangling; Song, Fengmei; Huo, Wenbo; Zhang, Shuxia; Chang, Junliang; Li, Jingliang; Zheng, Baisong; Liu, Yanqiu; Zhang, Yahong; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Recent epidemiological data indicate that outbreaks of hand, foot, and mouth disease (HFMD), which can be categorized according to its clinical symptoms as typical or atypical, have markedly increased worldwide. A primary causative agent for typical HFMD outbreaks, enterovirus 71 (EV71), has been shown to manipulate the cell cycle in S phase for own replication; however, it is not clear whether coxsackievirus (CVA6), the main agent for atypical HFMD, also regulates the host cell cycle. In this study, we demonstrate for the first time that CVA6 infection arrests the host cell cycle in G0/G1-phase. Furthermore, synchronization in G0/G1 phase, but not S phase or G2/M phase, promotes viral production. To investigate the mechanism of cell cycle arrest induced by CVA6 infection, we analyzed cell cycle progression after cell cycle synchronization at G0/G1 or G2/M. Our results demonstrate that CVA6 infection promotes G0/G1 phase entry from G2/M phase, and inhibits G0/G1 exit into S phase. Consistent with its ability to arrest cells in G0/G1 phase, the expression of cyclinD1, CDK4, cyclinE1, CDK2, cyclinB1, CDK1, P53, P21 and P16 is regulated by CVA6. Finally, the non-structural proteins of CVA6, RNA-dependent RNA polymerase 3D and protease 3C, are demonstrated to be responsible for the G0/G1-phase cell cycle arrest. These findings suggest that CVA6 induces G0/G1-phase cell cycle arrest in infected cells via non-structural proteins 3D and 3C, which may provide favorable conditions for virus production.